Experiencia estética y corporalidad: una lectura de la estética kantiana (2011)
ABSTRACT: Kant’s aesthetic thoughts and his art philosophy constitute a highlight within the discipline reflection of both phenomena. The fact is that the Kantian thinking, at the same time sets out a series of issues inherited from a very old tradition, also gives subsequent researches a reformulation that still determines our experiences about it. You could say that the originality of it does not lie as much in the discovery of theoretical horizons themselves, from which we have thought and experimented about the artistic and aesthetic matters; but rather in that peculiar way to elevate them at the level of fundamental philosophical issues. And also, in allowing their recognition as vital areas of human orientation in the world. But if necessary to attempt a brief statement that condense the most significant conquest of the Kantian labor, one might argue that because of it, a disciplinary autonomy is earned once and for all, which has, since then, set the standard of aesthetic and contemporary artistic studies.